Evaluation of Jute Leaf as Feed Ingredient for Labeo rohita Fingerlings - Singh, P.; Paul, B.N.; Rana, G.C.; Giri, S.S. (Indian Journal of Animal Nutrition, 2018)
A 60 day feeding trial was conducted to evaluate the suitability of jute (Corchorus olitorius) leaf powder, as a dietary protein source for Labeo rohita fingerlings. One control feed without jute leaf JL0 (0%) and four experimental feeds were prepared with graded levels of jute leaf powder viz; JL10 (10%), JL20 (20%), JL30 (30%) and JL40 (40%) respectively along with rice bran, soybean meal, mustard oil cake, vegetable oil and vitamin-mineral mixture. The feed with 20% of jute leaves (JL20) showed significantly (P